Synergistic therapeutic effect of arsenic trioxide and radiotherapy in BALB/C nude mice bearing nasopharyngeal carcinoma xenografts - Xie, L.X.; Lin, X.H.; Li, D.R.; Chen, J.Y.; Hong, C.Q.; Du, C.W. (Experimental Oncology, 2007)
It has been shown that arsenic trioxide (ATO) induced apoptosis in human nasopharyngeal carcinoma cells and inhibited the growth of nasopharyngeal carcinoma xenografts (NPCX) in nude mice. Aim: The present study was designed to determine whether ATO at the non-toxic dose level could potentiate the therapeutic effectiveness of radiation therapy in nasopharyngeal carcinoma, using a BALB/C nude mouse xenograft model. Methods: The mice bearing NPCX were treated with radiation alone (2, 4, and 6 Gy), ATO alone (4 mg/kg/day x 6 days), and ATO plus radiation at the same dosage levels. Time of tumor growth delay (defined as the time necessary for the tumor to grow four-fold of its initial volume after, compared with untreated tumors) and toxic effects were determined. Results: The low dose ATO alone has no pronounced effects on tumor growth delay compared to untreated control. However, compared with radiation alone, the combined regimen delayed the tumor growth by 2–10 days and had no significant toxic effects such as the liver function damage. Conclusions: Combination of ATO at non-toxic dose level and radiation has synergistic effects on tumor growth inhibition in vivo and is well tolerated. Установлено, что триоксид мышьяка (ТОМ) индуцирует апоптоз в клетках карциномы носоглотки человека и ингибирует
рост ксенографта карциномы носоглотки у атимических мышей. Цель работы — установить терапевтическую эффективность
радиотерапии в комбинации ТОМ в нетоксичной дозе мышам линии BALB/ с ксенографтом карциномы носоглотки.
Методы: животные с ксенографтом карциномы носоглотки получали либо только радиотерапию (2, 4 и 6 Гр) или ТОМ
(4 мг/кг/день в течение 6 дней), или их комбинацию в тех же режимах и дозах. Задержку роста опухоли определяли как
различие во времени, необходимом для достижения опухолью 4-кратного объема по сравнению с начальным объемом в
опытной группе versus такового в контрольной группе. Результаты: введение ТОМ в низкой дозе не оказывало выраженного
влияния на рост опухоли по сравнению с показателями в контрольной группе, а в комбинации с облучением приводило
к задержке роста опухоли на 2–12 сут по сравнению с показателями у животных, получавших только лучевую терапию
при отсутствии выраженных побочных эффектов. Выводы: комбинация ТОМ в нетоксической дозе и лучевой терапии
приводит к ингибированию роста опухоли in vivo и не вызывает побочных эффектов.
Ключевые слова: триоксид мышьяка, радиотерапия, ксенографт карциномы носоглотки.